2015
DOI: 10.1371/journal.pone.0123474
|View full text |Cite
|
Sign up to set email alerts
|

A De Novo Floral Transcriptome Reveals Clues into Phalaenopsis Orchid Flower Development

Abstract: Phalaenopsis has a zygomorphic floral structure, including three outer tepals, two lateral inner tepals and a highly modified inner median tepal called labellum or lip; however, the regulation of its organ development remains unelucidated. We generated RNA-seq reads with the Illumina platform for floral organs of the Phalaenopsis wild-type and peloric mutant with a lip-like petal. A total of 43,552 contigs were obtained after de novo assembly. We used differentially expressed gene profiling to compare the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 95 publications
(98 reference statements)
0
29
0
Order By: Relevance
“…Recently, the roles of B-and E-class MADS-box genes were revealed for orchid tepal development (Tsai et al, 2004;Tsai et al, 2005;Lu et al, 2007;Hsieh et al, 2013a;Su et al, 2013b;Pan et al, 2014;Hsu et al, 2015b;Huang et al, 2015;Huang et al, 2016). We have shown that knock-down expression of Eclass PeSEP1-4 genes reduced the expression of PeERF1.…”
Section: Peerf1 As a Downstream Target Of Floral Morphogenesis Genesmentioning
confidence: 99%
“…Recently, the roles of B-and E-class MADS-box genes were revealed for orchid tepal development (Tsai et al, 2004;Tsai et al, 2005;Lu et al, 2007;Hsieh et al, 2013a;Su et al, 2013b;Pan et al, 2014;Hsu et al, 2015b;Huang et al, 2015;Huang et al, 2016). We have shown that knock-down expression of Eclass PeSEP1-4 genes reduced the expression of PeERF1.…”
Section: Peerf1 As a Downstream Target Of Floral Morphogenesis Genesmentioning
confidence: 99%
“…were significantly altered in both genotypes (Huang et al 2015). Transcription factors (TFs) play a role in floral organ development.…”
Section: Regulation Ofmentioning
confidence: 99%
“…Of the 3,309 putative TF genes identified in the Phalaenopsis genome showed differences in expression between the wild-type and peloric mutant plants (Dataset S11). Notably, the PhAGL6b gene was upregulated in the peloric lateral inner tepals (liplike petals) and lip organs (Huang et al 2015). We therefore cloned the full-length sequence of…”
Section: Regulation Ofmentioning
confidence: 99%
“…Phalaenopsis or commonly known as 'Butterfly orchid', is one of the most popular orchids in the trade (Huang et al 2015). The Phalaenopsis genus comprises approximately 66 species that can be divided into five subgenera, namely Proboscidioides, Aphyllae, Parishianae, Polychilos and Phalaenopsis .…”
Section: Introductionmentioning
confidence: 99%
“…The Phalaenopsis genus comprises approximately 66 species that can be divided into five subgenera, namely Proboscidioides, Aphyllae, Parishianae, Polychilos and Phalaenopsis . These species are widely distributed in the Asia (India, Malaysia and Taiwan), Australia and the larger islands of the Pacific Ocean (Huang et al 2015). The plant is an epiphyte with fleshy, copious and adventitious roots arising from the base and lower nodes of stem.…”
Section: Introductionmentioning
confidence: 99%